THU0343 No Upregulation of IL-6 at Different Sites in Facet Joints of Patients with Ankylosing Spondylitis Compared to Controls. (23rd January 2014) - Bleil, J.; Syrbe, U.; Maier, R.; Appel, H.; Sieper, J.
Abstract : Background: The analysis of interleukin-6 serum levels in patients with ankylosing spondylitis (AS) have indicated that IL-6 might be a proinflammatory cytokine in AS patients. However, a placebo-controlled trail using Tocilizumab (TCZ) has failed to demonstrate the efficacy of the monoclonal humanized anti-human IL-6 receptor antibody TCZ over placebo for the treatment of symptoms of AS (Sieper et al., 2012, EULAR abstract [OP0166]). Objectives: An immunohistochemical analysis of IL-6 in facet joints from patients with AS in comparison to controls (CO) and osteoarthritis (OA) patients was performed to examine a possible reason for the missing efficacy of TCZ over placebo. Methods: Facet joints from 13 AS, 11 OA patients and 12 controls (autopsies without spinal diseases) were analyzed. Immunohistochemistry was performed to detect IL-6+ cells at five different sites: within subchondral bone marrow, fibrous tissue replacing subchondral bone marrow, hyaline cartilage, subchondral bone plate and at the enthesial sites. Results: The frequency of IL-6+ cells within subchondral bone marrow (p=0.0006), subchondral bone plates (p<0.0001), entheses (p=0.0003) and fibrous tissue replacing subchondral bone marrow (p=0.0327) was significantly lower and within hyaline cartilage slightly lower (p=0.1689) in patients with AS compared to OA. Most interestingly, no significant differences were observed at all analyzed sites if AS patients and controls were compared, with the exception of the subchondral bone marrow. Only there, a significant decrease of the IL-6 expression was evident in AS patients compared to both, OA (p=0.0006) and CO (p=0.0043), while OA patients even showed a significant increase compared to CO (p=0.0095). In addition, AS patients also tended to have even lower percentages of IL-6+ cells than controls regarding subchondral bone plates (p=0.2131) and entheses (p=0.0806). Conclusions: The comparable or even lower expression of IL-6 in facet joints of patients with AS compared to controls serves as a possible explanation for a lack of clinical benefit in the treatment of AS with anti-human IL-6 receptor antibody. References: Sieper et al., 2012, EULAR abstract [OP0166] Disclosure of Interest: None Declared